Pembuatan Arang Aktif Nanopartikel Kulit Nangka Menggunakan High Energy Milling dengan Aktivator H3PO4 - Safitri, Annisa Nur; Faris Al Ghifary, Muhammad; Widji Triana, Nurul; Nurma Wahyusi , Kindriari (Program Studi Teknik Kimia, Universitas Pamulang, 2024)
Activated charcoal is a compound formed from the arrangement of C atoms with a porous internal structure so that it has adsorption properties. One of the materials that can be used to make activated charcoal is jackfruit peel which contains cellulose (52.739%), lignin (10.599%), and hemicellulose (16.913%). Grind it to size of 100 mesh and put it in milling nanoparticles using tools HEM at a speed of 1200 rpm for 2 hours. Next, the activation process was carried out with phosphoric acid compounds and variables of 1 hour, 6 hours, 12 hours, 18 hours, 24 hours and concentrations of 5%, 10%, 15%, 20%, 25%. Samples in powder form were characterized by size, SEM, ash content and water content. Size test results with method Particle Size Analyzer (PSA) was found to be 1.22 nm. SEM test results show that jackfruit peel activated charcoal is composed of particles of diverse size, irregular shape and porous. EDX results showed that the chemical components of activated charcoal were C (57.08%), O (33.30%), Mg (1.33%), Si 1.57%, K 5.73%. Analysis of water content and ash content is the smallest, namely 0.18% and 0.2%.